2013
DOI: 10.1371/journal.pone.0066780
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Major Cardiovascular Risk Factors and the Association with Unhealthy Lifestyles in the Chinese Adult Population

Abstract: BackgroundPrevious studies indicated that lifestyle-related cardiovascular risk factors tend to be clustered in certain individuals. However, population-based studies, especially from developing countries with substantial economic heterogeneity, are extremely limited. Our study provides updated data on the clustering of cardiovascular risk factors, as well as the impact of lifestyle on those factors in China.MethodsA representative sample of adult population in China was obtained using a multistage, stratified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 26 publications
(22 reference statements)
2
38
0
1
Order By: Relevance
“…Among 46 239 Chinese adults recruited in 2007–2008 as a nationally representative cohort, the prevalence of having ≥2 risk factors was 55.3% 13. Another national study in 2009–2010 indicated that over half of Chinese adults with cardiovascular risk factors presented with a cluster of risk factors 14. Similar prevalent clustering of risk factors was also found in North China, South China15 16 and Northeast China (as presented in our study).…”
Section: Discussionsupporting
confidence: 86%
“…Among 46 239 Chinese adults recruited in 2007–2008 as a nationally representative cohort, the prevalence of having ≥2 risk factors was 55.3% 13. Another national study in 2009–2010 indicated that over half of Chinese adults with cardiovascular risk factors presented with a cluster of risk factors 14. Similar prevalent clustering of risk factors was also found in North China, South China15 16 and Northeast China (as presented in our study).…”
Section: Discussionsupporting
confidence: 86%
“…Among the CVD risk factors (CVDRFs) are hypertension, diabetes, smoking, dyslipidemia, and obesity [3,4]; these CVDRFs have been observed by our group [5,6].…”
Section: Introductionmentioning
confidence: 51%
“…Platelets, Early Online:[1][2][3][4][5][6][7] Platelets Downloaded from informahealthcare.com by University of Waterloo on 01/04/15For personal use only.…”
mentioning
confidence: 99%
“…For example, a study in China showed that the prevalence of clustering of cardiovascular disease risk factors (≥2 of hypertension, diabetes, dyslipidemia, or overweight) was 36% [52]. Also, a study in eight African countries and six countries in the Middle East found a similar pattern; their highest frequency was for subjects with two or three risk factors [53].…”
Section: Discussionmentioning
confidence: 99%